Dilemma of crystalloid resuscitation in non-exsanguinating polytrauma: what is too much? - van Wessem, Karlijn (Trauma Surg Acute Care Open, 2020)
BACKGROUND: Aggressive crystalloid resuscitation increases morbidity and mortality in exsanguinating patients. Polytrauma patients with severe tissue injury and subsequent inflammatory response without major blood loss also need resuscitation. This study investigated crystalloid and blood product resuscitation in non-exsanguinating polytrauma patients and studied possible adverse outcomes. METHODS: A 6.5-year prospective cohort study included consecutive trauma patients admitted to a Level 1 Trauma Center intensive care unit (ICU) who survived 48 hours. Demographics, physiologic and resuscitation parameters in first 24 hours, Denver Multiple Organ Failure scores, adult respiratory distress syndrome (ARDS) data and infectious complications were prospectively collected. Patients were divided in 5 L crystalloid volume subgroups (0–5, 5–10, 10–15 and >15 L) to make clinically relevant comparisons. Data are presented as median (IQR); p value <0.05 was considered significant. RESULTS: 367 patients (70% men) were included with median age of 46 (28–61) years, median Injury Severity Score was 29 (22–35) and 95% sustained blunt injuries. 17% developed multiple organ dysfunction syndrome (MODS), 4% ARDS and 14% died. Increasing injury severity, acidosis and coagulopathy were associated with more crystalloid administration. Increasing crystalloid volumes were associated with more blood products, increased ventilator days, ICU length of stay, hospital length of stay, MODS, infectious complications and mortality rates. Urgent laparotomy was found to be the most important independent predictor for crystalloid resuscitation in multinominal regression analysis. Further, fresh frozen plasma (FFP) <8 hours was less likely to be administered in patients >5 L compared with the group 0–5 L. With increasing crystalloid volume, the adjusted odds of MODS, ARDS and infectious complications increased 3–4-fold, although not statistically significant. Mortality increased 6-fold in patients who received >15 L crystalloids (p=0.03). DISCUSSION: Polytrauma patients received large amounts of crystalloids with few FFPs <24 hours. In patients with <10 L crystalloids, <24-hour mortality and MODS rates were not influenced by crystalloid resuscitation. Mortality increased 6-fold in patients who received >15 L crystalloids ≤24 hours. Efforts should be made to balance resuscitation with modest crystalloids and sufficient amount of FFPs. LEVEL OF EVIDENCE: Level 3. STUDY TYPE: Population-based cohort study.